METHODISM AND THE RISE OF POPULAR LITERARY CRITICISM - McInelly, Brett C. ([S.l.])
1 online resource
Keywords: This book examines how Methodism and popular review criticism intersected with and informed each other in the eighteenth century. Methodism emerged at a time when the idea of a public square' was taking shape, a process facilitated by the periodical press. Perhaps more so than any previous religious movement, Methodism, and the publications associated with it, received greater scrutiny largely because of periodical literature and the emergence of popular review criticism. The book considers in particular how works addressing Methodism were discussed and critiqued in the era's two leading literary periodicals - The Monthly Review and The Critical Review. Focusing on the period between 1749 and 1789, the study encompasses the formative years of popular review criticism and some of the more dramatic moments in the textual culture of early Methodism. The author illustrates some of the specific ways these review journals diverged in their critical approaches and sensibilities as well as their politics and religious opinions. The Monthly's and the Critical's responses to the Methodists' own publishing efforts as well as the anti-Methodist critique are shown to be both multifaceted and complex. The book critically reflects on the pretended neutrality, reasonableness, and objectivity of reviewers, who at times found themselves negotiating between the desire to regulate literary tastes and the impulse to undermine the Methodist revival. It will be relevant to scholars of religion, history and literary studies with an interest in Methodism, print culture, and the eighteenth century.